Transcendent Philosophy: The Ontological Realism of the Political Phenomenon - Mohammad Pezeshgi (‫سیاست متعالیه‏, 2021)
The present study aims to explore the existence of political phenomena through rational and argumentative inferences, using the teachings of transcendent philosophy. The purpose of political phenomena are the concepts, structures, and actions in which those structures occur. The present study claims that political phenomena are a shadow of the existence of science. Science has an independent and external presence in transcendent wisdom, and individuals enhance their existence by increasing political awareness (which emerges in culture, history, and collective identity). The political reality is adapted to the whole ontology of transcendent wisdom by proving the research claim. As a result, political phenomena are related to other existing objective facts, and it is possible to examine the ontological issues in question. One of the essential achievements of the present research for the philosophy of humanities is that it provides the possibility of designing the philosophical foundations of humanities-based on the teachings of transcendent wisdom.